Pembangunan Aplikasi Inventory Barang Berdasarkan Warehouse Management System (WMS) Di Sixpax Cloth - Evan Bastian; Oscar Hadikaryana (Universitas Kebangsaan Republik Indonesia, 2024)
Sixpax Cloth is located on the Trunojoyo Number. 30 Bandung, is a Distro that sells various types of products such as Tshirt, Gamis, Jackets, Jeans, Casuals, Shoes, Wallets and accessories. The business listing contained in the Sixpax cloth bandung warehouse is using a conventional system. The Inventory Management Application at Sixpax Mode Distro Bandung, is expected to facilitate data management and can present actual, efficient and efficient data.